Study of childhood renal tumours using a monoclonal antibody to Tamm-Horsfall protein. Issue 12 (December 1987) - Kumar, S; Marsden, H B; Jasani, B; Kumar, P
Abstract : A monoclonal antibody to Tamm-Horsfall glycoprotein was used for the immuno-localization of Tamm-Horsfall protein in formalin fixed, paraffin embedded tissue sections of childhood renal tumours, normal children's kidneys, and human fetal kidneys. The procedure was a dinitrophenyl hapten sandwich staining method. The antibody, diluted 1/100, 000, gave a very strong and specific staining of the loop of Henle and distal tubules of normal and fetal kidneys. No staining was seen in Wilms' tumour, mesoblastic nephroma, and bone metastasizing renal tumour of childhood. In contrast, two of seven renal carcinomas and three of four rhabdoid renal tumours were positive for Tamm-Horsfall protein.